Status Hukum Ketetapan MPR/S Setelah Perubahan UUD 1945 - Riri Nazriyah (Fakultas Hukum Universitas Islam Indonesia, 2005)
The decision of Legislative No.i/iegisiative Assemble/2003, demonstrates that the juridical issue relates to the obviousness ofthe substance andlegal status ofthesubstance andthe legal status ofthe GeneralAssembly (Temporary) has not beenremoved, because there some decisions which stiil exist. To solve the problems, the alternative solution is to convert the important substance which contains the decision ofthe Legislative Assembly (Temporaiy) into Law.